Regionalizacja międzynarodowego sądownictwa karnego z perspektywy zasady komplementarności na przykładzie proponowanego Afrykańskiego Trybunału Sprawiedliwości oraz Praw Człowieka i Ludów: [The regionalization of international criminal justice from the perspective of the complementarity principle on the example of the proposed African Court on Human and Peoples’ Rights] (Studia Prawnicze / The Legal Studies, 2019)
Artykuł odnosi się do tendencji regionalizacji międzynarodowego sądownictwa karnego, jak np. planów rozszerzenia jurysdykcji Afrykańskiego Trybunału Sprawiedliwości oraz Praw Człowieka i Ludów, z perspektywy zasady komplementarności. Opracowanie zmierza do udowodnienia, że tradycyjne rozumienie komplementarności (jako alokacji jurysdykcji pomiędzy Międzynarodowym Trybunałem Karnym a sądami krajowymi) można rozwinąć tak, aby uwzględnić także regionalne trybunały karne – jako szczebel pośredni pomiędzy stałym MTK a sądownictwem krajowym. Ze względu na zachodzące na siebie – choć nie tożsame – zakresy jurysdykcji, można potraktować MTK i trybunał regionalny jako potencjalnych partnerów, a nie konkurentów, w sądzeniu zbrodni międzynarodowych. The present contribution deals with recent trends of regionalizing international criminal justice, as in the case of the proposed extension of jurisdiction of the African Court of Justice and Human and People’s Rights over international crimes, and examines them against the background of the principle of complementarity, whose classic aim would be to allocate jurisdiction between the International Criminal Court and national courts. It is argued that the traditional understanding of complementarity may be extended to accommodate also regional criminal tribunals. A regional layer of criminal jurisdiction would therefore be introduced between the ICC and national courts. Given the overlapping but not identical scopes of jurisdiction, by the ICC, and the African Court, respectively, it is possible to conceive of them as potential partners working in parallel terms in prosecuting international (and transnational) crimes.